PENGARUH PEMBERIAN VERMIKOMPOS DAN INTERVAL PEMBERIAN AIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN STEVIA (Stevia rebaudiana Bertoni) - Dewi, Lara Putri Kartika; Setiyono, Setiyono; Ristiyana, Suci; Tanzil, Ahmad Ilham; Meliala, Susan Barbara Patricia Sembiring; Nisak, Fauziatun; Savitri, Dyah Ayu; Arum, Ayu Puspita (Program Studi Agribisnis Fakultas Pertanian, 2024)
Stevia plant, as an alternative to sugarcane, is a plant that is susceptible to drought. The growth and yield of the stevia plant is highly dependent on the availability of sufficient water and nutrients. To get optimal crop yields is necessary to pay attention to the water needs of the stevia-growing media. The right intensity of watering and using organic fertilizers are efforts that can be done to prevent drought. This study aimed to determine the effect of vermicompost and water application intervals on the growth and yield of stevia plants. A divided plot design was used in this study with 12 treatment combinations with three replications. The basic pattern of completely randomized design (CRD) consists of 2 factors with three replications. The main plot is the interval of giving water (I), namely I1 = 1 day, once, I2 = once every 2 days, I3 = once every 3 days and Subplots, namely the dose of vermicompost, consist of 4 levels, namely V0 = 0 tons/ha, V1 = 5 tons /ha, V2 = 10 tons/ha, V3 = 15 tons/ha. The data were analyzed using analysis of variance. The significant difference between treatments is determined using Duncan's Multiple Distance Test at 5%. The best watering interval is the interval of giving once every three days and vermicompost 5 tons/ha.